Pseudotachylyte-Mylonites Record of Transient Creep From Inter-Seismic Ductile to Co-Seismic Rupture - Dai, Wenhao; Zhou, Yongsheng; Ma, Xi (Frontiers in Earth Science, 2022)
Transient creep during an earthquake cycle is very important to understand the rheology of fault and deformation mechanisms in the brittle-plastic transition zone. In this paper, the samples collected from the Red River Fault, southwest of China, where there were exposed a series of ductile to brittle deformed fault rocks which recorded transient creep related to earthquake, were systematically observed under optical microscope, SEM and EBSD to analyze the microstructures of deformation. The results show that mylonties formed at the inter-seismic creep was overprinted by pseudotachylyte which is the product of the coseismic rupture and crack healing during the post-seismic relaxion. Based on the analysis of the deformation mechanism of fault rocks, the brittle-plastic transition during seismic cycle in the Red River fault is demonstrated by an oscillation deformation model.